(untitled) (Journal of the College of Basic Education, 2023)
In this study the interaction between Iraqi Bentonite clay and Melamine was estimated by using FT-IR and XRD methods these methods indicate the Melamine molecule form interlayer complex with Bentonite unit crystal sheets through Hydrogen bonding and electrostatic forces this interaction increase the space dimension among clay sheets, the obtained complex was used to prepare the second complex by reaction with formaldehyde. The XRD pattern and FT-IR spectra show that the formation of the polymer was happen inside the space among clay sheets and the formatted polymer cause an irreversible change in the crystal structure of Bentonite that form the complex with polymer.